Single-dose dexamethasone increases perioperative glycemic variability in older patients with diabetes undergoing lung surgery: a continuous glucose monitoring-based randomized controlled trial - Xiaoyi Zhang; Cheng Huang; Xiang Wang; Jun Zhang; Xiaomei Ling; Jiahao Xu; Jue Ma; Fei Zhong; Haihua Shu (Frontiers in Medicine, 2026)
Objectives To investigate whether a single intraoperative dose of dexamethasone alters perioperative glycemic dynamics in older patients with type 2 diabetes undergoing thoracoscopic lung resection. Glycemic dynamics were captured using continuous glucose monitoring (CGM). Methods 72 patients aged ≥ 60 years with type 2 diabetes who underwent elective thoracoscopic lung resection were randomly assigned to receive either 8 mg of dexamethasone or placebo (0.9% saline) intravenously during anesthesia induction. The primary outcome was the maximum change in intraoperative blood glucose from preoperative baseline. Key secondary outcomes included CGM-derived glycemic variability (GV) metrics, including standard deviation (SD), coefficient of variation (CV), blood glucose instability index (GLI) and time-in-range measures, assessed throughout the perioperative period. Multivariable linear regression was performed to assess the independent effect of dexamethasone on glycemic outcomes after adjusting for relevant covariates. The accuracy of CGM was assessed using mean absolute relative difference and Bland-Altman analysis. Results The dexamethasone group exhibited greater median (IQR) maximum intraoperative glucose change: 3.6 (3.3–4.9) mmol/L vs. 3.1 (2.6–4.0) mmol/L; P = 0.009. Dexamethasone was also associated with higher intraoperative GV: SD (1.1 [1.0–1.4] mmol/L vs. 0.8 [0.7–1.0] mmol/L, P < 0.001), CV (21.9 [6.3] vs. 15.8 [6.1]; P < 0.001), and GLI (3.0 [1.7–4.1] mmol 2 /L 2 /h vs. 1.4 [0.9–2.4] mmol 2 /L 2 /h; P < 0.001). Multivariable analysis confirmed that dexamethasone independently predicted greater intraoperative glucose excursions and glycemic variability. Perioperative time-in-range metrics did not differ significantly between groups. CGM demonstrated acceptable accuracy in this surgical setting. Conclusion A single 8 mg intraoperative dose of dexamethasone increases maximum intraoperative glucose change and amplifies GV in older patients with diabetes. These findings reveal a previously uncharacterized dimension of dexamethasone-induced glycemic instability in this vulnerable population and highlight the need for glycemic monitoring strategies that capture transient fluctuations potentially missed by conventional intermittent measurements. Clinical trial registration www.chictr.org.cn , identifier [ChiCTR2300077167].